Development and initial validation of the career resilience instrument for CDC emergency responders in China within the context of public health emergencies: based on a survey conducted in Shanghai - Wang, An-Qi; Cheng, Wen-Di; Fu, Yu-Yan; Luo, Ya-Shuang; Li, Juan; Wang, Hai-Yin; Jin, Chun-Lin (Frontiers in Public Health, 2024)
Background: China faces various public health emergencies, and emergency responders at the Centers for Disease Control and Prevention (CDC emergency responders) are the a mainstay in responding to public health emergencies. Career resilience can help CDC emergency responders to effectively respond to and recover from public health emergencies, but there is no specific measurement instrument available. This In this study, we aimed aims to develop and conduct an initial validation of the career resilience instrument for CDC emergency responders in China within the context of public health emergencies from a process perspective.Based on a survey conducted in Shanghai, Iinterpretive phenomenological analysis (IPA), which is a qualitative research approach to describing and analyzing individual experiences, was used to analyze the interview texts to develop the initial career resilience instrument for CDC emergency responders. The initial career resilience instrument was revised through two rounds of expert consultation.Cronbach's  coefficient and exploratory factor analysis were used to test the reliability and validity of the revised career resilience instrument.The initial career resilience instrument for CDC emergency responders contained three first-level measurement dimensions, nine second-level measurement dimensions, and fifty-two measurement items. After expert consultation, the first-level and second-level measurement dimensions were not revised, thirteen measurement items were deleted or revised, and six measurement items were added, resulting in a generation of forty-eight measurement items. The revised career resilience instrument was tested for good reliability and validity.Conclusions: Career resilience for CDC emergency responders can be regarded as a set of protective factors and dynamic processes that can be cultivated and intervened in cognitive, affective, and behavioral dimensions to improve their ability to respond to and recover from public health emergencies.